Advanced robotics and intelligent automation in manufacturing - Habib, Maki K., 1955- (IGI Global, Engineering Science Reference, 2020)
"This book examines recent advances and state-of-the-art technologies in the field of robotics engineering and mechatronics for advanced intelligent manufacturing"-- provided by publisher.
Keywords: Manufacturing processes -- Automation -- Handbooks, manuals, etc.; Robots, Industrial -- Handbooks, manuals, etc.; elektronické knihy; electronic books